13 A randomised trial of expedited transfer to a cardiac arrest centre for non-ste out-of-hospital cardiac arrest: arrest. (25th January 2018) - Patterson, Tiffany; Perkins, Gavin D; Joseph, Jubin; Wilson, Karen; Dyck, Laura Van; Robertson, Steven; Nguyen, Hanna; McConkey, Hannah; Whitbread, Mark; Fothergill, Rachael; Nevett, Joanne; Dalby, Miles; et al.
Abstract : Background: Wide variation exists in inter-hospital survival from OHCA. Regionalisation of care into cardiac arrest centres (CAC) may improve this. We report a pilot randomised trial of expedited transfer to a CAC following OHCA without ST-elevation. The objective was to assess the feasibility of performing a large-scale RCT. Methods: Adult witnessed VF OHCA of presumed cardiac cause were randomised 1:1 to either: (1) intervention: expedited transfer to a CAC for goal-directed therapy including access to immediate reperfusion, or (2) control: current standard of care involving delivery to the geographically closest hospital. The feasibility of randomisation, protocol adherence and data collection of the primary (30 day all-cause mortality) and secondary (cerebral performance category (CPC)) and in-hospital major cardiovascular and cerebrovascular events (MACCE) clinical outcome measures were assessed. Results: Between Nov 2014 and April 2016, 118 cases were screened, of which 63 patients (53%) met eligibility criteria and 40 of the 63 patients (63%) were randomised. There were no protocol deviations in the treatment arm. Data collection of primary and secondary outcomes was achieved in 83%. There was no difference in baseline characteristics between the groups: 30 day mortality (Int 9/18, 50% vs Control 6/15, 40%; p=0.73), CPC 1/2 (Int: 9/18, 50% vs Control 7/14, 50%; p>0.99) or MACCE (Int: 9/18, 50% vs Control 6/15, 40%; p=0.73). Conclusions: These findings support the feasibility of conducting a large-scale RCT to address a remaining uncertainty in post-arrest care.